2016
DOI: 10.1111/eth.12498
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Discrimination of Shoal Size in the Guppy (Poecilia reticulata)

Abstract: For a diversity of species, differences in sexual and parental roles, along with differences in body morphology, often result in males and females having different diets, distinct predators and even different patterns of habitat use. As a consequence, the two sexes often face different environmental challenges and selection may favour the evolution of sex differences in cognition. We tested this prediction in the guppy (Poecilia reticulata). Under perceived hazard, individual guppies join the larger available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 77 publications
2
39
0
Order By: Relevance
“…Moreover, we predicted that the sexes would diverge in cognitive style where a ‘fast-exploratory’ learning type (e.g. faster decision making, shorter latencies to sample) would be more associated with males as has been found in other poeciliids [7]. Lastly, we predicted that the sexes would diverge in their relationship between cognitive domains.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, we predicted that the sexes would diverge in cognitive style where a ‘fast-exploratory’ learning type (e.g. faster decision making, shorter latencies to sample) would be more associated with males as has been found in other poeciliids [7]. Lastly, we predicted that the sexes would diverge in their relationship between cognitive domains.…”
Section: Introductionmentioning
confidence: 79%
“…In previous fish studies examining sex differences in cognitive styles during associative learning assays with food rewards (T maze [43], visual discrimination of shapes and colors [44]) researchers have found a fast-exploratory cognitive style associated with males , not females. Only during shoal discrimination tasks in poeciliids (guppies, Gambusia ) have females been shown to make faster decisions than males [7]. If strong sexual selection pressures have shaped female Gambusia shoaling decision-making processes, perhaps this has influenced the cognitive style in general numerical discrimination tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should use caution in interpreting results from few subjects because within-species differences between fish can occur (Gierszewski et al, 2013;Lucon-Xiccato, Dadda, & Bisazza, 2016;Miletto Petrazzini & Agrillo, 2016;Schluessel et al, 2012Schluessel et al, , 2015Siebeck et al, 2009;Wyzisk & Neumeyer, 2007). However, other studies have utilized two to five goldfish per experiment or test (Douglas, Eva, & Guttridge, 1988;Freche et al, 2012;Neumeyer, 1992Neumeyer, , 2003Wyzisk & Neumeyer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences have been previously described in spatial learning in fish, and most studies have found greater male performance (Carazo et al 2014, Fabre et al 2014, Saucier et al 2008, Jonasson 2005 but see Jones et al 2003, Healy et al 1999. Importantly, behavior exhibited during a task can vary by sex independently of cognitive performance (Burns & Rodd 2008, Mamuneas et al 2015Lucon-Xiccato & Bisazza 2016;Etheredge et al 2018;Titulaer 2012, Dougherty & Guillette 2018, for instance due to where males are typically identified as the "bolder" or "more exploratory" sex (Lucon-Xiccato & Dadda 2016, Han et al 2015, Harris et al 2010, Overli et al 2006, Gagnon et al 2016, but see Hughes 1968& Swanson 1966. Regardless, if the ecological demands of the social environment are largely invariant over time for one or both sexes, one might expect robust sex differences in cognition.…”
Section: Introductionmentioning
confidence: 98%